The ameliorative effects of Tualang honey mediated silver nanoparticles on hippocampal damages following kainic acid administration in male rats - Hasim, Hidani; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Pasupuleti, Visweswara Rao; Sangu, Muthuraju; Mohd, Asnizam Asari (2022)
Kainic acid (KA) was shown to be associated in the mechanism of excitotoxicity-induced neurodegeneration in the brain. Tualang honey (TH) was reported to have protection against neurodegeneration but no study has explored on its silver nanoparticles (THSN). Therefore, present study aimed to investigate the effects of THSN on glutathione status and hippocampal histology in KA-induced rats. Sprague-Dawley rats (n=42) were divided into seven groups such as control, THSN 10 mg, THSN 50 mg, KA alone, THSN 10 mg + KA, THSN 50 mg + KA and Topiramate + KA, and each group were pretreated orally with either distilled water, THSN (10 mg/kg or 50 mg/kg) or Topiramate (40 mg/kg), respectively, five times at 12 h intervals. Saline or KA (15 mg/kg body weight) were injected subcutaneously 30 min after last oral treatment. All animals were sacrificed 24 h post KA injection and the hippocampus was harvested for histological examination using cresyl violet staining. The reduced glutathione (GSH) and oxidized glutathione (GSSG) was determined using commercially available ELISA kits. The significant (p<0.05) decrease in the level of cresyl violet-positive cells in hippocampal CA3 in KA alone group was ameliorated by THSN (10 mg/kg) pretreatment group. Meanwhile, the KA induced reduction in GSH:GSSG ratio in KA alone group was significantly (p<0.05) increased by both doses of THSN pretreatments. In conclusion, THSN showed potential protective effects by improving the glutathione status and reduce hippocampal cells injury in the rats after KA induced.